2018
DOI: 10.1017/s0954579418000895
|View full text |Cite
|
Sign up to set email alerts
|

Are Whites and minorities more similar than different? Testing the cultural similarities hypothesis on psychopathology with a second-order meta-analysis

Abstract: The cultural differences hypothesis is the assertion that there are large differences between Whites and racial/ethnic minorities in the United States, while there are small differences between- (e.g., African Americans and Latinos) and within- (e.g., Latinos: Mexican Americans and Cuban Americans) minority groups. Conversely, the cultural similarities hypothesis argues that there are small differences between Whites and minorities, and these differences are equal or smaller in magnitude than differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 104 publications
(145 reference statements)
0
32
0
Order By: Relevance
“…Furthermore, some meta-analyses were expected to have overlapping samples because meta-analyses can include some of the same primary studies, which would violate the meta-analytic assumption of independence (Becker, 2000). In past research, an overlap less than or equal to 25% was considered acceptable (Causadias et al, in press; Zell et al, 2015). Thus, we examined the overlap of studies included in each average association by cross-referencing the included primary studies and dividing the number of duplicate studies by the number of studies included in each meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some meta-analyses were expected to have overlapping samples because meta-analyses can include some of the same primary studies, which would violate the meta-analytic assumption of independence (Becker, 2000). In past research, an overlap less than or equal to 25% was considered acceptable (Causadias et al, in press; Zell et al, 2015). Thus, we examined the overlap of studies included in each average association by cross-referencing the included primary studies and dividing the number of duplicate studies by the number of studies included in each meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For this reason, it is also important to synthesize meta-analytic research to converge at a more representative mean of the distribution. A second-order meta-analysis can facilitate this accumulation because it averages across meta-analytic effects to provide the most comprehensive estimate of an association (see Causadias, Korous, & Cahill, in press).…”
Section: The Importance Of Research Synthesismentioning
confidence: 99%
“…Finally, Causadias, Korous, and Cahill (2018) studied the cultural differences hypothesis (i.e., that there are large differences between Whites and minorities, while there are small differences between- and within-minority groups) and the cultural similarities hypothesis (i.e., that there are small differences between Whites and minorities, and these differences are equal or lesser than differences between- and within-minorities). They conducted a second-order meta-analysis on levels of psychopathology with 16 meta-analyses on 493 primary studies ( N = 3,036,749) and found support for the cultural similarities hypothesis.…”
Section: Understanding Cultural Differences and Similarities In Develmentioning
confidence: 99%
“…First, our findings provide additional evidence that mental disorders, including hierarchical conceptualizations of them, may be robust to "ethnic bias" (Eaton et al, 2013). In a recent meta-analysis, group differences in symptom counts and rates of diagnoses between EA and non-EA individuals were found to be small across several mental disorders (Causadias et al, 2018). These results were detected after having accounted for developmental period (i.e., childhood or adolescence), age, sex, years of education, and the type of measure of psychopathology (i.e., interview or questionnaire) (Causadias et al, 2018).…”
Section: Discussionmentioning
confidence: 54%
“…In a recent meta-analysis, group differences in symptom counts and rates of diagnoses between EA and non-EA individuals were found to be small across several mental disorders (Causadias et al, 2018). These results were detected after having accounted for developmental period (i.e., childhood or adolescence), age, sex, years of education, and the type of measure of psychopathology (i.e., interview or questionnaire) (Causadias et al, 2018). Similarly, small effect sizes were detected with respect to racial-ethnic group differences in the prevalence rates of the mental disorders in the PNC sample.…”
Section: Discussionmentioning
confidence: 98%